1993
DOI: 10.1038/hdy.1993.48
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of life history in Daphnia magna. I. Heritabilities at two food levels

Abstract: Broad-and narrow-sense heritabilities for several life-history traits were estimated from 23 mother-daughter pairs of Daphnia magna at two food levels. Sexually produced daughter clones were obtained from a field collection of ephippial females (mothers) and the subsequent hatching of their ephippial eggs (daughters). Mother and daughter clones were maintained by parthenogenetic reproduction. Heritabilities of adult body-length of eight successive instars were the highest estimates of all in good food, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 27 publications
6
53
0
1
Order By: Relevance
“…In some experiments, V A increases with greater stress or environmental novelty (Holloway et al 1990;Pigliucci et al 1995;Imasheva et al 1998), in some there is no change (Bubli et al 1998;Hoffmann & Schiffer 1998;Merilä & Fry 1998) and in others there is a decrease (Kasule 1991;Ebert et al 1993;Blows & Sokolowski 1995;Kawecki 1995;Sgrò & Hoffmann 1998a,b). Note that many of these studies obtain different results for different traits.…”
Section: Introductionmentioning
confidence: 99%
“…In some experiments, V A increases with greater stress or environmental novelty (Holloway et al 1990;Pigliucci et al 1995;Imasheva et al 1998), in some there is no change (Bubli et al 1998;Hoffmann & Schiffer 1998;Merilä & Fry 1998) and in others there is a decrease (Kasule 1991;Ebert et al 1993;Blows & Sokolowski 1995;Kawecki 1995;Sgrò & Hoffmann 1998a,b). Note that many of these studies obtain different results for different traits.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of other traits in D. melanogaster and of other environmental factors also revealed increases of narrow heritability in response to an increase in the stressfullness of the environment, such as for longevity in response to gamma-radiation dose (Westerman & Parsons, 1973), for adult survival time in response to ethanol vapour concentration (Parsons, 1982;van Herrewege & David, 1984) and to acetic acid concentration (Parsons, 1982), for sternopleural cheatae number in response to temperature (Sclinee & Thompson, 1984) and for larval development time in response to citric acid concentration of 574 the larval growth medium (Ward, 1985). Analogous findings have been reported using other organisms and include increased heritability of lead tolerance in the plant Festuca ovina with increasing lead contamination of the soil (Urquhart,1 971), an accelerated response to selection for timing of the first clutch in the cotton stainer bug Dysdercus bimaculatus with increasing moisture stress (Derr, 1980), an increase of narrow heritability for both female development time and for instantaneous mortality rate in the rice weevil Sitophilus oryzae after transfer to a more stressful diet (Holloway eta!., 1990) and an increase of narrow heritability for clutch size in the water flea Daphnia magna in response to food deprivation (Ebert et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that nutrient and temperature have significant effects on the life cycles of the planktonic species (Ebert et al 1993, Gillooly 2000and Savage et al 2004 which in turn affected the population growth of zooplanktons. This was evident in C. reticualta cultured in cowdung medium up to a certain range (25-29 o C) of temperature.…”
Section: Resultsmentioning
confidence: 99%